Impact of focused gamma ray beam angle on the response of density logging tool. (May 2017) - Wu, He; Zhang, Feng; Guo, Hongbo; Xin, Yi; Han, Zhongyue
Abstract: The response of the gamma-gamma density logging tool with different focused gamma ray beam angle is investigated by using the MCNP code. This work focuses on the four aspects of spatial distribution and energy spectrum of scattered gamma rays, measurement uncertainty, the depth of investigation, and vertical resolution of the logging tool. The results show that the density measurement accuracy can be improved when a relative larger collimator angle is employed, and the vertical resolution of the tool would not get worse. Highlights: A benchmarked MCNP model of density well logging was built. Focused gamma ray beam angle play a significant role in the response of density logging. Method for improving the accuracy of density measurement.